No–till planting of black gram for enhancing productivity in the NE Himalayas - Singh, Raghavendra; Avasthe, R K; Babu, Subhash (Indian Farming, 2020)
North-Eastern Himalayan Region (NER) of the country is hotspot of biodiversity. The regionis favourable for pulses cultivation. The soil and agro-climatic conditions provide the strongfoundation for pulses production in the region. However, in spite of all the favourable conditions,the region has a deficit of almost 82% of its pulses requirement. Although, the averageproductivity of pulses in NER (848 kg/ha) is higher than the National average (764 kg/ha),indicating the potential of pulses production in this region. The gap of requirement has to bereduced with the adoption of appropriate package of practices viz. short-duration varieties,conservation tillage, mulching, adjustment of sowing time, integrated nutrient and pestmanagement etc. In the region, pulses are being grown in rice (Oryza sativa L.) and maize(Zea mays L.) fallow areas. Adoption of no-till and in-situ residue retention for moistureconservation are the main component for enhancing the productivity in the region.